How PIDs & Preprints Are Facilitating The Ownership Of African Scholarly Content - Owango, Joy; Havemann, Jo (My University, 2021)
As part of the NISO.plus conference 2021 in the session "Quality and reliability of preprints, Ms Joy Owango presented the work AfricArXiv and TCC Africa are doing in facilitating ownership of African scholarly content using persistent identifiers.
Keywords: Interoperability; Persistent Identifiers; Data Communications